The Plant-Dependent Life Cycle of Thecaphora thlaspeos: A Smut Fungus Adapted to Brassicaceae - Lamprinos Frantzeskakis; Kaitlyn J. Courville; Lesley Plücker; Ronny Kellner; Julia Kruse; Andreas Brachmann; Michael Feldbrügge; Vera Göhre (Molecular Plant-Microbe Interactions, 2017)
Smut fungi are globally distributed plant pathogens that infect agriculturally important crop plants such as maize or potato. To date, molecular studies on plant responses to smut fungi are challenging due to the genetic complexity of their host plants. Therefore, we set out to investigate the known smut fungus of Brassicaceae hosts, Thecaphora thlaspeos. T. thlaspeos infects different Brassicaceae plant species throughout Europe, including the perennial model plant Arabis alpina. In contrast to characterized smut fungi, mature and dry T. thlaspeos teliospores germinated only in the presence of a plant signal. An infectious filament emerges from the teliospore, which can proliferate as haploid filamentous cultures. Haploid filaments from opposite mating types mate, similar to sporidia of the model smut fungus Ustilago maydis. Consistently, the a and b mating locus genes are conserved. Infectious filaments can penetrate roots and aerial tissues of host plants, causing systemic colonization along the vasculature. Notably, we could show that T. thlaspeos also infects Arabidopsis thaliana. Exploiting the genetic resources of A. thaliana and Arabis alpina will allow us to characterize plant responses to smut infection in a comparative manner and, thereby, characterize factors for endophytic growth as well as smut fungi virulence in dicot plants.